(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Left ventricular hypertrophy (LVH) is a common cardiovascular abnormality in patients with chronic kidney disease (CKD) and may play a contributory role in the progression of renal dysfunction. Objective: To determine the association between left ventricular hypertrophy and the stage of chronic kidney disease, and to evaluate whether LVH serves as an independent predictor of CKD progression. Methods: This was a cross-sectional analytical study conducted at Tertiary Care Hospitals from November 2024 to April 2025. A total of 235 patients with diagnosed chronic kidney disease (CKD) were included in the study. Demographic details, clinical history, CKD stage, comorbidities (such as hypertension, diabetes mellitus), and laboratory parameters (including serum creatinine and eGFR) were documented using a structured proforma. Results: LVH was present in 143 patients (60.9%), with significantly higher prevalence in advanced CKD stages (74.3%) compared to early stages (36.1%, p < 0.001). Patients with LVH had lower eGFR (22.6 ± 10.3 vs. 41.4 ± 13.1 mL/min/1.73m², p < 0.001) and higher systolic blood pressure. A significant inverse correlation was observed between LVMI and eGFR (r = –0.462, p < 0.001). Logistic regression revealed LVH as an independent predictor of advanced CKD (aOR: 3.26, 95% CI: 1.84–5.77, p < 0.001). Conclusion: Left ventricular hypertrophy is strongly associated with advanced chronic kidney disease and may serve as an early marker of disease progression. Routine cardiac screening in CKD patients could facilitate early risk stratification and targeted management to potentially delay renal deterioration.